Religious personality and perceived behavior among faith-practicing communities in Malaysia: uniting or dividing factors? - Idris, Fazilah; Hamzah, Azimi; Tamam, Ezhar; Wong, Su Luan; Mastor, Khairul Anwar; Suradi, Nur Riza (Common Ground Research Networks, 2008)
This paper aims to report the findings on the contribution of religious personality, as the manifestation of one’s religious belief, on the interethnic behavior. Religious personality is comprised of three major factors: pro-social behavior, ritual behavior and anti-social behavior. While religious practice is categorized into high, medium, low and not practicing. It is hypothesized that religious personality of the youth may influence interethnic behavior by enhancing a mutual understanding and respect. Respondents were 563 high school students from randomly selected schools in Selangor. Instruments used were the Inter-ethnic Tolerance Questionnaire (IETQ) a self-designed questionnaire to measure interethnic perceived behavior and the Universal Religious Personality Inventory (URPI) (Krauss et al., 2006). The findings of the study indicated that religious personality traits of types pro-social behavior and ritual behavior have significant effects on inter-ethnic tolerant behavior. Also for students with high and medium levels of religious practice, pro-social behavior is found to significantly influence their inter-ethnic tolerant behavior. The higher their mean scores for pro-social behavior, the more positive are their tolerant behavior on inter-ethnic issues.